Developing an optimised method for accurate wear testing of dental materials using the ‘Rub&Roll’ device - Maier, Eva; Ruben, Jan; Palin, William M.; Bronkhorst, Ewald; Olmos, Manuel; Matta, Ragai; Loomans, Bas (Scientific Reports, 2024)
Dental materials are challenged by wear processes in the oral environment and should be evaluated in laboratory tests prior to clinical use. Many laboratory wear-testing devices are high-cost investments and not available for cross-centre comparisons. The ‘Rub&Roll’ wear machine enables controlled application of force, chemical and mechanical loading, but the initial design was not able to test against rigid antagonist materials. The current study aimed to probe the sensitivity of a new ‘Rub&Roll’ set-up by evaluating the effect of force and test solution parameters (deionized water; water + abrasive medium; acid + abrasive medium) on the wear behaviour of direct and indirect dental resin-based composites (RBCs) compared with human molars against 3D-printed rod antagonists. Molars exhibited greater height loss than RBCs in all test groups, with the largest differences recorded with acidic solutions. Direct RBCs showed significantly greater wear than indirect RBCs in the groups containing abrasive media. The acidic + abrasive medium did not result in increased wear of RBC materials. The developed method using the ‘Rub&Roll’ wear machine in the current investigation has provided a sensitive wear test method to allow initial screening of resin-based composite materials compared with extracted human molars under the influence of different mechanical and erosive challenges.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Abrasion; Dental materials; Erosion; Laboratory test method; Resin-based composites; Wear